'A Collation of Badly Disguised, Well-Known Themes': Shostakovich Symphonies in the Parisian Press, 1936–1946. Issue 2 (June 2023) - ROYCROFT, MADELINE
Abstract: This article examines the reception of Shostakovich's symphonies in the Parisian press, from the late interwar period to the years immediately following the Second World War. In doing so, it continues the conversation around international responses to Shostakovich's music in the twentieth century, adding a consideration of the composer's symphonies in France from 1936 to 1946 to the existing literature on Shostakovich reception in the United States, Britain, and Germany. By interrogating the commentary of Parisian critics and music writers during this period, the article reveals how the reception of Shostakovich's symphonies in Paris reflects the rising and falling influence of the French Communist Party, and offers a novel way to view the shifts in Franco-Soviet relations either side of the Second World War.